PENGARUH SHIFT KERJA DAN KOMUNIKASI TERHADAP EFEKTIVITAS KERJA KARYAWAN DI PT DEV SUKSES GROUP TANGERANG - Salimin, Sahril; Isep Amas Priatna (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of work shifts and communication on work effectiveness both partially and simultaneously. The research method used is quantitative with data collection techniques by means of field research, namely observation and questionnaire, literature study and data analysis. The population in this study were employees of PT Dev Sukses Group with a total of 52 people, saturated sampling technique, the number of samples in this study were 52 respondents. The results of this study are 1) The work shift has no significant effect on work effectiveness with the regression equation Y = 25.691 + 0.171X1, the correlation value of 0.155 means that the two variables have a very low level of relationship. The coefficient of determination is 2.4% and the hypothesis test obtained t count < t table or (1.107 < 1.674). Thus H0 is accepted and H1 is rejected, meaning that there is no significant effect of work shifts on work effectiveness. 2) communication has a significant effect on work effectiveness with the regression equation Y = 14.604 + 0.493X2 correlation value of 0.456 meaning that the two variables have a moderate level of relationship. The coefficient of determination is 20.8% and the hypothesis test obtained t count> t table or (3.621> 1.675). Thus H0 is rejected and H2 is accepted, meaning that there is a significant effect of communication on work effectiveness. 3) Shift work and communication simultaneously have a significant effect on work effectiveness with the regression equation Y = 12.433 + 0.081X1 + 0.478X2. The correlation value of 0.461 means that the independent variable and the dependent variable have a moderate level of relationship. The coefficient of determination is 21.3% while the remaining 79.7% is influenced by other factors. Hypothesis testing obtained Fcount> Ftabel or (6.629> 3.18). Thus H0 is rejected and H3 is accepted. This means that there is a significant effect simultaneously work shift and communication on work effectiveness.